AUTOMATED CONTROL SYSTEMS OF SHORT-TERM COURSES AND THEIR PLACE IN THE ASC OF UNIVERSITY DEPARTMENT - Kryvakovska, R. V. (Science and Transport Progress, 2009)
Main prerequisites for creation of automated control systems for short-term courses of qualification upgrading are analyzed in this article. Also main tasks for the system are considered, the system structure are given. Some issues on its realization are considered as well.